The Role of Collaboration and Digital Technology in Supply Chain Management in Micro Enterprises - Siskawati, Eka; Syaputra, Hafiz; Zahara, Zahara (International Ecsis Association, 2024)
Micro businesses have revived, and many have sprung up after the COVID-19 pandemic, including the Coffee Shop micro business. In addition, technological developments in the increasingly rapid digital era have provided nuances and dynamics in research in micro-enterprise supply chains. This study aims to explore supply chain management behavior in micro-enterprises in the era of digital technology. This research contributes to enriching knowledge from research on micro-enterprise agility after the COVID-19 pandemic. This research strategy uses a qualitative approach that allows the author to conduct an in-depth analysis and sort the data into themes. Data was collected from a micro-scale coffee shop in Padang City, North East Coffee Shop. This paper found that (1) the best strategy is to collaborate with small roasteries that are more open to micro-scale coffee shops. (2) The coffee shop micro business has a level of technology adoption to support its operations. This research contributes to enriching knowledge from research on micro-enterprise agility after the COVID-19 pandemic.